PERCEIVED CAREER PLANNING AND JOB SATISFACTION IN MALAYSIAN ARMED FORCES: THE ROLE OF CAREER DEVELOPMENT AS A MEDIATOR - Hasan Al-Banna Mohamed; Hishamuddin Mohd Som; Norashikin Sahol Hamid; Mohd Hamran Mohamad (International Journal of Management Studies, 2023)
This study examines the relationship between career planning and job satisfaction of Armed Forces personnel in Malaysia. It determines the mediating effect of career development on the relationship between career planning and job satisfaction. This study was conducted because there is negligible attention given to the effects of career planning and career development on job satisfaction, mainly in the Malaysian Armed Forces context. The IBM Social Science Statistical Package (IBM SPSS) application was used in the data analysis using descriptive and inferential analysis. The outcomes displayed three important findings: First, the significant relationship between career planning and job satisfaction. Second, the relationship between career development and job satisfaction was significant. Third, the result statistically confirms that the effect of career planning on job satisfaction is indirectly affected by career development in the organisational sample. Further, the study discusses the contributions and recommendations based on the significant findings. In conclusion, the career planning among Malaysian Armed Forces personnel should be explained and aligned with their career development since it will affect their job satisfaction and increase their work performance in national defence and security.